Quantum private function evaluation - Zhu Cao (New Journal of Physics, 2023)
Private function evaluation (PFE) is a task that aims to obtain the output of a function while keeping the function secret. So far its quantum analog has not yet been articulated. In this study, we initiate the study of quantum PFE (QPFE), the quantum analog of classical PFE. We give a formal definition of QPFE and present two schemes together with their security proofs. We then give an experimental demonstration of the scheme. Finally we apply QPFE to quantum copy protection to illustrate its usage.